2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24884
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supplemental Instruction on the Performance of Male and Female Engineers in a Freshman Chemistry Course

Abstract: Emily is a senior chemical engineering student at Northeastern University with a minor in biochemical engineering. She has been a chemistry tutor for freshman engineering students for the past three years. Miss Rachel Lauren Shapiro, Northeastern UniversityRachel Shapiro is a third year undergraduate student studying chemical engineering at Northeastern University. She has been involved in the Connections Chemistry Review program for the past 2 years. Rachel works in a chemical engineering lab on campus, has h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Female students with between 0 and 20 pre-enrollment college credits had a 2.10-times higher odds than students entering with 20 or more college credits of using first-year SI two or more times (p=0.0004, 95% CI: 1.39, 3.16). These results also corroborate our previous findings that students who were more confident that they would receive a high grade in a first-year general chemistry course at the beginning of the course had a higher average grade threshold for seeking SI [26] and that females had a higher trigger point for seeking SI than males [27]. Our current findings suggest that students with less pre-matriculation exposure to rigorous college engineering curricula are less academically prepared to excel in college compared to those with greater exposure to collegelevel studies.…”
Section: Si Use Pre-college Education and Gendersupporting
confidence: 90%
“…Female students with between 0 and 20 pre-enrollment college credits had a 2.10-times higher odds than students entering with 20 or more college credits of using first-year SI two or more times (p=0.0004, 95% CI: 1.39, 3.16). These results also corroborate our previous findings that students who were more confident that they would receive a high grade in a first-year general chemistry course at the beginning of the course had a higher average grade threshold for seeking SI [26] and that females had a higher trigger point for seeking SI than males [27]. Our current findings suggest that students with less pre-matriculation exposure to rigorous college engineering curricula are less academically prepared to excel in college compared to those with greater exposure to collegelevel studies.…”
Section: Si Use Pre-college Education and Gendersupporting
confidence: 90%
“…[17] Data from previous studies of the effect of SI on success of females and males in a first-semester freshman chemistry course support these claims. [18] [14] [19] Many studies also suggest that female students not only have a more positive attitude towards their studies but also are more intrinsically interested in learning and coursework. [20] …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that academic help, among other types of support, has a positive impact on the retention of women in engineering. Our previous research has shown that female tutees are more responsive to peer tutoring and take the initiative to seek tutoring more often than their male counterparts [2] - [4]. From the tutor's perspective, Espinoza and Cole have reported that peer tutoring enhanced the academic performance of female tutors, but not male tutors within a group of 229 students in STEM [15].…”
Section: Effects Of Leadership Roles On Women In Stemmentioning
confidence: 99%